2000
DOI: 10.1182/blood.v96.6.2081
|View full text |Cite
|
Sign up to set email alerts
|

Depressed immunity and impaired proliferation of hematopoietic progenitor cells in patients with complete spinal cord injury

Abstract: The bone marrow is supplied with both sensory and autonomic neurons, but their roles in regulating hematopoietic and immunocompetent cells are unknown. Leukocyte growth and activity in patients with stable and complete spinal cord injuries were studied. The innervation of the bone marrow below the injury level lacked normal supraspinal activity, that is, a decentralized bone marrow. Lymphocyte functions were markedly decreased in injured patients. Long-term colony formation of all hematopoietic cell lineages, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 17 publications
4
43
1
Order By: Relevance
“…Hence it appears that the ability to mount a nonadaptive granulocytic response remains intact in the patients. This contrasts somewhat with our previous observation that the lymphocyte-mediated non-specific (NK cell) and adaptive (B and T lymphocyte) immunity were markedly reduced in otherwise healthy subjects with spinal cord injury (Iversen et al, 2000). The numbers of blood leucocyte subsets were apparently not different among the three study groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Hence it appears that the ability to mount a nonadaptive granulocytic response remains intact in the patients. This contrasts somewhat with our previous observation that the lymphocyte-mediated non-specific (NK cell) and adaptive (B and T lymphocyte) immunity were markedly reduced in otherwise healthy subjects with spinal cord injury (Iversen et al, 2000). The numbers of blood leucocyte subsets were apparently not different among the three study groups.…”
Section: Discussioncontrasting
confidence: 99%
“…The numbers of the very immature, uncommitted CD34 + CD38 ) cells never exceeded 2% of the total number of CD34 + cells, and were similar among the three study groups (data not shown). Although the numbers of these early progenitor cells are apparently unchanged in spinal cord injured subjects, their proliferative capacity was found to be substantially reduced when assessed in vitro as the colony growth of long-term colony initiating cells (Iversen et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Yes [25,32,40] HLA-DR Reduced expression (blood) N/D [25,35] B lymphocyte Reduced number (immature and mature), genesis, and humoral function; more pronounce deficiency in centralized tissues (spleen, BM). Secondary humoral response is unaffected (spleen)…”
Section: Immune Component Alteration Following Sci and Evaluated (Tismentioning
confidence: 99%
“…This reduced lymphocyte activity most likely reflects a qualitative defect. 21 Data on granulocyte function though, is more controversial, with some concluding that neutrophils have a significantly impaired phagocytic function, for example, in complete tetraplegics while others have reported that granulocyte function is normal in SCI patients. 22,23 Cerebral stroke may also result in immunosupression, possibly as a result of sympathetic signaling to the lymphoid organs.…”
Section: Altered Intrinsic Defence Mechanismsmentioning
confidence: 99%